Team Sport Risk Exposure Framework-2 (TS-REF-2) to identify sports activities and contacts at increased SARS-CoV-2 transmission risk during the COVID-19 pandemic - Jones, B.; Phillips, G.; Beggs, C.; Calder, J.; Cross, M.; Pearce, N.; Readhead, C.; Smith, J.; Stokes, K. A.; Kemp, S. (British Journal of Sports Medicine, 2021)
The Team Sports Risk Exposure Framework (TS-REF) was developed in July 2020 by experts in sports medicine, virology, sports science and public health to facilitate the safe return of sport during the COVID-19 pandemic. The TS-REF was developed at the time when the outdoor transmission risk of SARS-CoV-2 during sport was unknown. The TS-REF has been adopted by Public Health England and the UK Government (Department for Digital, Culture, Media and Sport), for use within both elite and community sports, to both determine the risk of SARS-CoV-2 transmission during specific sporting activities (eg, rugby tackle), and to identify and isolate increased risk contacts during sport.3 The TS-REF classified increased risk contacts as player-to-player interactions `within 1 m, directly face to face, for 3 or more seconds`.